Development and Assessment of a Gastroscopy Electronic Learning System for Primary Learners: Randomized Controlled Trial - Li, Shuang; Li, Guoqing; Liu, Ying; Xu, Wanying; Yang, Ningning; Chen, Haoyuan; Li, Ning; Luo, Kunpeng; Jin, Shizhu (JMIR Publications, 2020)
BackgroundEndoscopic examination is a popular and routine procedure for the diagnosis and treatment of gastrointestinal (GI) diseases. Skilled endoscopists are in great demand in clinical practice, but the training process for beginners to become endoscopy specialists is fairly long. Convenience and a self-paced, learner-centered approach make electronic learning (e-learning) an excellent instructional prospect. ObjectiveThis study aimed to develop and apply an e-learning system in gastroscopy teaching and learning and to evaluate its effectiveness and user satisfaction. MethodsThe e-learning software Gastroscope Roaming System was developed for primary learners. The system simulates the real structure of the upper gastrointestinal (UGI) tract to teach the main characteristics of gastroscopy under both normal conditions and conditions of common UGI tract diseases. A randomized controlled trial was conducted. Participants were randomly allocated to an e-learning group (EG)or a non-e-learning control group after a pretest. On completing the training, participants undertook a posttest and gastroscopy examination. In addition, the EG completed a satisfaction questionnaire. ResultsOf the 44 volunteers, 41 (93%) completed the gastroscopy learning and testing components. No significant pretest differences were found between the intervention and control groups (mean 50.86, SD 6.12 vs mean 50.76, SD 6.88; P=.96). After 1 month of learning, the EG's posttest scores were higher (mean 83.70, SD 5.99 vs mean 78.76, SD 7.58; P=.03) and improved more (P=.01) than those of the control group, with better performance in the gastroscopy examination (mean 91.05, SD 4.58 vs mean 84.38, SD 5.19; P<.001). Overall, 85% (17/20) of the participants were satisfied with the e-learning system, and 95% (19/20) of the participants considered it successful. ConclusionsE-learning is an effective educational strategy for primary learners to acquire skills in gastroscopy examination and endoscopic imaging of the GI tract. Trial RegistrationChinese Clinical Trial Registry ChiCTR-IOR-17013091; http://www.chictr.org.cn/showproj.aspx?proj=22142